Changes in hydrological characteristics of the Ob River caused by climate change in 1922–2020 (according to the observations in Barnaul) - Svetlana Yu. Samoilova; Elena V. Mardasova; Andrey A. Kolomeytsev (Известия Томского политехнического университета: Инжиниринг георесурсов)
Relevance. Violation of hydrological characteristics stationarity caused by climate change and the necessity to take into account the flow change in hydrological studies and prognoses. Aim. To assess the hydrological characteristics evaluation and analyze the Ob River flow directional changes near the city of Barnaul and the flow-forming factors related to the changes (air temperature and precipitations according to the Barnaul meteorological station data). Methods. Complex geographic-hydrological analysis; statistical analysis of time series including the evaluation of the time series homogeneity with the use of the Fisher and Student criteria, the Pettitt’s, Buishand’s and Alexandersson’s tests; directional changes linear rends estimation. Results and conclusions. The authors have examined the meteorological and hydrological characteristics series stationarity according to Barnaul gauging station and Barnaul meteorological station from 1922 to 2020 with the annual, seasonal, and monthly resolution and detected the years with the time series homogeneity violations. Based on the conditionally selected homogenous periods the quantitative assessment of the average monthly and seasonal flow was performed. The linear trends of the average and maximum water flow and level, air temperature and precipitations were examined, their significance was assessed. The climate reasons for the Ob River flow changes were detected. During the study it was established that the hydrological characteristics series stationarity violation is caused by the climate flow-forming factors changes, predominantly by the air temperature changes. The main changes of the flow lie in its redistribution within a year. A statistically significant increase in winter low water discharge was marked, the figures being 20–30 %. During the seasonal flood the discharge increases in April and decreases in May and June, however, these changes are not statistically significant. There was a decrease of the maximum water discharge and level as well as the dispersion reduction of the annual and maximum flow amid the increase of the annual average discharge of water, which indicates a natural flow regulation. The flow changes in the winter low water and seasonal flood go beyond natural fluctuations as the meltwater and base-flow ratio significantly changed. The new quasistationary period of the Ob River upper course starts in the 80s of the 20th century unlike the rivers in the European part of Russia, the violation of the time-series stationarity of which is correlated to the intense temperature increase in the 70s of the 20th century.